Perilaku Swamedikasi - Laurensius Amedeo Sitindaon (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Self-medication is the behavior of consuming the medication itself based on the diagnosis of the symptoms that occur. Self-medication is part of "self-care" which is an effort to maintain health or prevent and overcome disease. The use of herbal or traditional medicines and medicines obtained by reusing or sending back previous prescriptions is also included in self-medicated behavior. Self-medicated behavior in Indonesian society is high. Objective: To find out about the terms, benefits, risks, and rational use of drugs in self-medicated behaviour. Method: The method used is a literature study which aims to summarize the current understanding of the topic by summarizing previously published discussion topics. Results: Self-medication including buying drugs by reusing / sending back previous prescriptions, taking medicines on the advice of family or others, and consuming leftover medicines. The main factors underlying self-medicated behavior are expensive drugs and medical expenses, lack of education and knowledge in the health sector. Self-medication provides an inexpensive, fast, and convenient solution to treating minor ailments if it is done based on the rational use of medicine. Self-medication will save you more time and money in finding health facilities. Self-medicated behavior can lead to various health problems if done incorrectly.